Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 186751 by 073 last updated on 09/Feb/23

Answered by Rasheed.Sindhi last updated on 09/Feb/23

f(x)=ax^2 +bx+c  f(x−1)+f(x)+f(x+1)=x^2 +1  f(2)=?     a(x−1)^2 +b(x−1)+c        +ax^2 +bx+c               +a(x+1)^2 +b(x+1)+c                          =x^2 +1  ax^2 −2ax+a+bx−b+c       +ax^2 +bx+c               +ax^2 +2ax+a+bx+b+c                          =x^2 +1  3ax^2 +3bx+2a+3c=x^2 +1  3a=1⇒a=1/3  3b=0⇒b=0  2a+3c=1⇒2(1/3)+3c=1  ⇒c=1/9  f(x)=(1/3)x^2 +(1/9)  f(2)=(1/3)(2)^2 +(1/9)=(4/3)+(1/9)=((13)/9)

f(x)=ax2+bx+cf(x1)+f(x)+f(x+1)=x2+1f(2)=?a(x1)2+b(x1)+c+ax2+bx+c+a(x+1)2+b(x+1)+c=x2+1ax22ax+a+bxb+c+ax2+bx+c+ax2+2ax+a+bx+b+c=x2+13ax2+3bx+2a+3c=x2+13a=1a=1/33b=0b=02a+3c=12(1/3)+3c=1c=1/9f(x)=13x2+19f(2)=13(2)2+19=43+19=139

Answered by a.lgnaoui last updated on 09/Feb/23

f(x−1)+f(x+1)+f(x)=  a[(x−1)^2 +(x+1)^2 +x^2 ]+b[3x]+3c  =a(3x^2 +2)+3bx+3c   { ((3ax^2 +3bx+(2a+3c)=x^2 +1)),((a=(1/3) ;  b=0 ;    c=(1/9) )) :}  f(x)=(1/3)x^2 +(1/9)  donc       f(2)=((13)/9)

f(x1)+f(x+1)+f(x)=a[(x1)2+(x+1)2+x2]+b[3x]+3c=a(3x2+2)+3bx+3c{3ax2+3bx+(2a+3c)=x2+1a=13;b=0;c=19f(x)=13x2+19doncf(2)=139

Answered by CElcedricjunior last updated on 10/Feb/23

f(x)=ax^2 +bx+c  f(0)=c  f(1)=a+b+c  f(2)=4a+2b+c  f(3)=9a+3b+c  f(−1)=a−b+c  f(−1)+f(0)+f(1)=1  =>2a+2b+c=1 (1)  f(0)+f(1)+f(2)=c+a+b+c+4a+2b+c=2  =>5a+3b+3c=2 (2)  f(1)+f(2)+f(3)=a+b+c+4a+2b+c+9a+3b+c=5  14a+6b+3c=5 (3)   { ((2a+2b+c=1)),((14a+6b+3c=5)) :}5a+3b+3c=2  c=1−2a−2b   5a+3b+3−6a−6b=2  =>−a−3b=−1 (4)  14a+6b+3−6a−6b=5  =>8a=2=>a=(1/4)■Moivre  b=(1/3)(1−(1/3))=(2/9)  c=1−(4/9)−(2/4)=1−((16+18)/(36))=1−((34)/(36))=1−((17)/(18))=(1/(18))  f(x)=(1/4)x^2 +(2/9)x+(1/(18))  f(2)=1+(4/9)+(1/(18))=1+(9/(18))=((27)/(18))=(3/2)  f(2)=(3/2)★ celebre cedric junior

f(x)=ax2+bx+cf(0)=cf(1)=a+b+cf(2)=4a+2b+cf(3)=9a+3b+cf(1)=ab+cf(1)+f(0)+f(1)=1=>2a+2b+c=1(1)f(0)+f(1)+f(2)=c+a+b+c+4a+2b+c=2=>5a+3b+3c=2(2)f(1)+f(2)+f(3)=a+b+c+4a+2b+c+9a+3b+c=514a+6b+3c=5(3){2a+2b+c=114a+6b+3c=55a+3b+3c=2c=12a2b5a+3b+36a6b=2=>a3b=1(4)14a+6b+36a6b=5=>8a=2=>a=14Moivreb=13(113)=29c=14924=116+1836=13436=11718=118f(x)=14x2+29x+118f(2)=1+49+118=1+918=2718=32f(2)=32celebrecedricjunior

Commented by Rasheed.Sindhi last updated on 10/Feb/23

Good approach!  (But check for errors.)

Goodapproach!(Butcheckforerrors.)

Commented by CElcedricjunior last updated on 12/Feb/23

ok thank!

okthank!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com